Should we dump the metabolic syndrome?: Yes - Gale, Edwin A M (BMJ Publishing Group Ltd., 2008)
The number of people with the metabolic syndrome is rising alongside obesity. Nevertheless, Edwin Gale believes the diagnosis has little practical value. George Alberti and P Z Zimmet, however, think it increases the detection of people at high risk of diabetes and heart disease